2014
DOI: 10.9790/2380-07713143
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity of Some Indigenous Collections of Upland Taro [Colocassia esculenta var. antiquorium (L.) Schott] for Selection of Genotypes Aiming at Improvement in Breeding Programme

Abstract: Upland taro [Colocassia esculenta var. antiquorium (L).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Singh et al [85] reported high variability among 859 taro accessions from Papua New Guinea using 10 quantitative and 20 qualitative traits. High morphological variability has also been reported among taro accessions from Southeast Asia and Oceania [86,87]. Similar agro-morphological variability was observed among 2,298 taro accessions collected within the TaroGen project [88].…”
Section: Taro Germplasm Characterizationsupporting
confidence: 67%
“…Singh et al [85] reported high variability among 859 taro accessions from Papua New Guinea using 10 quantitative and 20 qualitative traits. High morphological variability has also been reported among taro accessions from Southeast Asia and Oceania [86,87]. Similar agro-morphological variability was observed among 2,298 taro accessions collected within the TaroGen project [88].…”
Section: Taro Germplasm Characterizationsupporting
confidence: 67%
“…Similarly, Bhattacharjee et al reported wide degree of variation in leaf colour and shape corm weight and number of petiole per plant existed among different selected genotypes in India indicating greater possibility of improvement through selection [28]. Such quantitative and qualitative morphological variation might contribute desirable character that has to be included in breeding for further improvement of the crop.…”
Section: Morphological Characterizationmentioning
confidence: 97%
“…Many researchers have also reported the presence of high variability in the taro using morphological markers [16]. Corm color, corm shape, corm size, petiole length, number of petioles, petiole color, corm flesh color, leaf color, leaf shape, corm weight, stolon formation [17][18][19], and flower formation [20] are just a few of the morphological markers.…”
Section: Variability In Taromentioning
confidence: 99%